Refsum's Disease—Use of the Intestinal Lipase Inhibitor, Orlistat, as a Novel Therapeutic Approach to a Complex Disorder. (1st September 2010) - Perera, Nimalie J.; Lewis, Barry; Tran, Huy; Fietz, Michael; Sullivan, David R.
Abstract : Refsum's Disease is an inherited metabolic disorder in which a metabolite of branched chain fatty acids accumulates due to lack of appropriate oxidative enzymes. Patients have elevated plasma phytanic acid levels and high concentrations of phytanic acid in a variety of tissues leading to progressive tissue damage. Besides retinal degeneration or retinal dystrophy associated with adult onset retinitis pigmentosa, additional symptoms include chronic polyneuropathy, cerebellar ataxia, sensorineural hearing loss, anosmia, ichthyosis, as well as skeletal, cardiac, hepatic, and renal abnormalities. Current management includes avoidance of dietary sources of branched chain fatty acids and regular plasmapheresis to prevent accumulation of these compounds to ameliorate progressive neurological deficits. Two brothers with Refsum's disease who experienced progressive symptoms despite optimal diet and plasmapheresis were commenced on a novel therapy. We report the effect of the intestinal lipase inhibitor, Orlistat, which led to significant reduction (P - value < 0.001 on 2-sample unpaired t -test) of mean preplasmapheresis phytanic acid levels with retardation of the progression of most of their dermatological and neurological symptoms.